Should we treat aging as a disease? The consequences and dangers of miscategorisation - Faragher, Richard G. A. (Frontiers in Genetics, 2015)
The ageing of the population represents one of the largest healthcare challenges facing the world today. The available evidence shows that interventions are available now that can target fundamental ‘ageing’ processes or pathways. These could significantly impact either individual age-linked pathologies or the broader failure of organ systems that occurs with ageing leading in both cases to improved later life health within a relatively short time scale (less than ten years). Sufficient economic evidence is available to argue convincingly that this approach will also save enormous sums of money which could then be deployed to solve other urgent global problems. However, as yet this transformative ‘win-win’ scenario has barely entered the public consciousness and, far from being a point of vigorous debate, seems to be ignored by policy makers. Understanding why this lethargy exists is important given the urgent need to deal with the challenge represented by population ageing. In this paper I postulate that one major cause of inaction is a widely held, but flawed, conceptual framework concerning the relationship between ageing and disease that categorises the former as ‘natural’ and the latter as ‘abnormal’.